Uji Kinerja Bioeraktor Hibrid Anaerob Dua Tahap Dengan Variabel Beban Kejut (Shock Loading) Pada Pengolahan Limbah Cair Pabrik Kelapa Sawit - Khairat, Nur; Ahmad, Adrianto; Yenie, Elvi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The progress of plantation area in Indonesia to increase significantly. Along with the increasing area of oil palm plantations, the production of palm oil mills also increase. The production of palm oil mill produced wastewater with high content of organic material. If it discharged into the water, it will potentially to reduced water quality and pollute the environment. Wastewater treatment can be anaerobically by using hybrid anaerobic bioreactor. This research purposed to test the stability and performance of hybrid anaerobic bioreactor two stage with shock loading variable measured the content of COD (chemical oxygen demand), pH, temperature and production of biogas. The operation of shock loading is by providing the rate loading increase suddenly of 50% with the flow rate is 7.5 L/day, increase of 100% with the flow rate is 10 L /day and increase of 150% with the flow rate is 12.5 L/day for 6 hours, then returned to flow rate base of first bioreactor with the flow rate is 5 L/day. The results of testing the stability of the bioreactor in anticipation the fluctuations of wastewater flow with shock loading by 50%, 100% and 150% showed that the recovery period of hybrid anaerobic bioreactor two stage relatively quickly with time span is 5 to 7 days. The highest COD reduction is obtained after loading increase 150% at flow rate 12.5 L/day, COD value is 4.500 mg/L with COD removal efficiency is 92.2%. Therefore, the flow rate increase suddenly (shock loading) wasn’t effect the performance of hybrid anaerobic bioreactor two stage so the process of wastewater treatment can take place properly.Keywords: Anaerobic , COD, Palm Oil Mill Wastewater, Shock Loading, Two Stage Anaerobic Bioreactor Hybrid.